Educação de jovens e adultos: práticas sociais de leitura, construindo múltiplas identidades - Patricia Guimaraes Vargas (2010)
The present research aims to increase the understanding of the literacy and psychological development process of adults, by the investigation of how they appropriate of the senses and meanings in reading, looking for outline in which reading practices they are inserted, constitute themselves as readers and construct multiple identities. This ethnographic research focused on a classroom of Adult Education in a public school in the city of Belo Horizonte, through participant observation, field notes, collection and analysis of artifacts from the group, interviews, photographs, video and audio recordings and conversation and reading circles. The theoretical and methodological focus adopted is based on the historical-cultural approach, based on the assumptions of the Interactional Sociolinguistics and Critical Discourse Analysis of the Interactional Ethnography (SBCDG, 1992), Lev S. Vygotskys social theory of knowledge construction (VYGOTSKY, 2005, 2006, 2008), Paulo Freires literacy and awareness process (FREIRE, 1980, 1996, 2007, 2008) and Mikhail Bakhtins enunciative language theory (BAKHTIN, 1992). The interactions and interventions experienced in the classroom and the ones produced in the data-generating activities consisted themselves in opportunities in which students have expressed and exchanged their views and perceptions of the world and knowledge. These mediations made the construction of meaning in reading possible and promoted the practice of Metacognition for both the teacher favoring the analysis and reflection over their pedagogic practice and planning and the learning process of the adult learners. The analysis of the students discourses and of the contrast between two lessons of this class made visible the amplitude in which each one of them rebuilt and reframed their social practices of reading and their self images, reconfiguring, therefore, multiple identities.